2014
DOI: 10.3168/jds.2013-6599
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection strategies in a small dairy cattle population evaluated for genetic gain and profit

Abstract: The objective of this study was to evaluate a genomic breeding scheme in a small dairy cattle population that was intermediate in terms of using both young bulls (YB) and progeny-tested bulls (PB). This scheme was compared with a conventional progeny testing program without use of genomic information and, as the extreme case, a juvenile scheme with genomic information, where all bulls were used before progeny information was available. The population structure, cost, and breeding plan parameters were chosen to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…This poses a challenge for their future genetic gain relative to breeds with large reference populations. Thomasen et al (2014) showed that low reliabilities of genomic prediction is the single most important factor that limits the genetic gain in smaller populations with more intensive use of young bulls without a progeny test. The aim of this paper is to review theory and practical results on strategies and methods to increase the accuracies of GEBV in numerically small dairy populations.…”
Section: Introductionmentioning
confidence: 99%
“…This poses a challenge for their future genetic gain relative to breeds with large reference populations. Thomasen et al (2014) showed that low reliabilities of genomic prediction is the single most important factor that limits the genetic gain in smaller populations with more intensive use of young bulls without a progeny test. The aim of this paper is to review theory and practical results on strategies and methods to increase the accuracies of GEBV in numerically small dairy populations.…”
Section: Introductionmentioning
confidence: 99%
“…There are also other conflicting goals such as genetic diversity, genetic uniqueness or specific local conditions. However, even in small dairy cattle populations, genomic breeding schemes are genetically (Kariuki et al, 2014;Thomasen et al, 2014a), as well as economically superior to conventional breeding schemes (Thomasen et al 2014a). This superiority is lower than estimated for larger populations, as the major limitation for small populations is the comparatively low accuracy of genomic predictions (Kariuki et al, 2014;Thomasen et al, 2014a).…”
mentioning
confidence: 99%
“…However, even in small dairy cattle populations, genomic breeding schemes are genetically (Kariuki et al, 2014;Thomasen et al, 2014a), as well as economically superior to conventional breeding schemes (Thomasen et al 2014a). This superiority is lower than estimated for larger populations, as the major limitation for small populations is the comparatively low accuracy of genomic predictions (Kariuki et al, 2014;Thomasen et al, 2014a). Consequently, it is difficult to implement more efficient and at the same time more cost-effective breeding schemes (Thomasen et al, 2014a), although, in terms of genetic gain, reduced accuracies are partially compensated by shortened generation intervals (Kariuki et al, 2014).…”
mentioning
confidence: 99%
“…They concluded that raising the accuracy of GEBV would result in further increase of profit. In another study, Thomasen et al (2014) reported 13% higher discounted profit in response to 40% improvement in the accuracy of a three-trait selection index in a small population. In these studies, the additional costs associated more individuals being genotyped was not considered; therefore, their estimated discounted profit could be overestimated.…”
Section: Resultsmentioning
confidence: 93%
“…Zhou et al 2013;Su et al 2014). K€ onig et al (2009) and Thomasen et al (2014) evaluated the potential effects of increasing genotyping cost and accuracies on discounted profit of genomic selection schemes without considering the costs related to increase in the number of individuals in the training set and recording their daughters. B€ orner and Reinsch (2012) assessed optimisation of genomic breeding programme under a cost limitation strategy, without incorporating the cost of performance recording of bulls' daughters in training set.…”
Section: Introductionmentioning
confidence: 99%